Trimethylamine N‐Oxide Aggravates Liver Steatosis through Modulation of Bile Acid Metabolism and Inhibition of Farnesoid X Receptor Signaling in Nonalcoholic Fatty Liver Disease. Issue 17 (22nd May 2019) - Tan, Xuying; Liu, Yan; Long, Jingan; Chen, Si; Liao, Gongcheng; Wu, Shangling; Li, Chunlei; Wang, Lijun; Ling, Wenhua; Zhu, Huilian
Abstract : Scope: Trimethylamine N ‐oxide (TMAO), the metabolite of choline generated by gut microbiota, is associated with nonalcoholic fatty liver disease (NAFLD) and could influence bile acid (BA) metabolism. However, whether TMAO aggravates liver steatosis by modulating BA metabolism and the related mechanisms has not been investigated. Methods and results: A case‐control study including biopsy‐proven NAFLD patients ( n  = 34) and controls ( n  = 14) is conducted to determine the correlation between TMAO and BA metabolism. Serum levels of total BA and the percentage of farnesoid X receptor (FXR)‐antagonistic BA species are markedly higher in NAFLD patients than in the controls. Serum levels of TMAO positively correlated with the serum levels of total BA and hepatic mRNA expression of cholesterol 7 alpha hydroxylase (CYP7A1). In a murine model, it is found that 18 weeks administration of TMAO impairs liver function and increases hepatic triglyceride accumulation and lipogenesis in mice fed with a high‐fat diet. TMAO increases BA synthesis and shifted hepatic BA composition toward FXR‐antagonistic activity. Knockdown of CYP7A1 via small interfering RNA or activation of FXR by GW4064 blocks the effect of TMAO‐induced lipogenesis in palmitic acid‐treated HepG2 cells. Conclusion: TMAO aggravates liver steatosis by suppressing BA‐mediated hepatic FXR signaling. Abstract : Trimethylamine N ‐oxide modulates bile acid metabolism, resulting in increased bile acid synthesis and a marked shift to a farnesoid X receptor (FXR)‐antagonistic bile acid profile. Consequently, hepatic FXR activity is suppressed and the expression levels of genes related to lipogenesis are upregulated, thus accelerating triglyceride synthesis.